Synthetic strategies for pyrrolo[2,1-f][1,2,4]triazine: the parent moiety of antiviral drug remdesivir - Rai, Gaurav S. (Chem Heterocycl Compd (N Y), 2021)
[Image: see text] This review summarizes diverse synthetic protocols for the preparation of pyrrolo[2,1-f][1,2,4]triazine derivatives, covering literature sources from the past two decades. For effective representation, the synthetic methods toward the title compound are classified into six distinct categories: 1) synthesis from pyrrole derivatives, 2) synthesis via bromohydrazone, 3) synthesis via formation of triazinium dicyanomethylide, 4) multistep synthesis, 5) transition metal mediated synthesis, and 6) rearrangement of pyrrolooxadiazines. A brief outline of all optimized schemes is provided with relevant examples.